A method for stiffness tuning of machine tool supports considering contact stiffness. (March 2015) - Kono, Daisuke; Nishio, Syuya; Yamaji, Iwao; Matsubara, Atsushi
Abstract: A methodology for tuning the stiffness of machine tool supports is described based on a stiffness model using the contact stiffness approach. Using this model, the mathematical relationship between the load of the support and its stiffness is established. The relationship is separated into three regions. When the total stiffness of all supports is maximized, the load must be tuned so that the stiffness–support load relationship is in the critical region, whereby the contact stiffness is slightly larger than the bulk stiffness. Correspondingly, a placement method of supports is proposed that increases their stiffness without anchor bolts. The effectiveness of the proposed method is verified in two experiments. In the first experiment, the natural frequency of a small machine tool prototype is compared for several placements of three supports. The lowest natural frequency of the machine tool under the proposed placement scheme is maximized. In the second experiment, the proposed method is applied to increase the lowest natural frequency of a horizontal milling machine. The lowest natural frequency with a distinct arrangement of three supports is increased by 15–55%, compared to other popular placements of these three supports. The experimental results show that the proposed placement method is effective for enhancing the stiffness of machine tool supports. Highlights: A method for tuning stiffness of machine tool supports is proposed. The relationship between stiffness and support preload must be considered. The lowest natural frequency was increased compared to popular placements. The proposed method is effective for enhancing stiffness of machine tool supports.